Macrophage PTP1B regulates mitochondrial dynamics via the JAK2/STAT3-OPA1 axis and activates the cGAS/STING signaling pathway - Lei, Xuefeng; Qian, Diandian; Zhang, Wenzheng; Zhao, Bin’an; Li, Yabin; Hao, Hua; Yuan, Jing; Zhao, Le; Liu, Centao (Frontiers in Immunology, 2025)
Tendinopathy is characterized by degenerative changes in tendon tissue, with its pathogenesis closely associated with macrophage-mediated chronic inflammation and mitochondrial dysfunction. Bioinformatics analysis of tendinopathic tissues revealed a significant upregulation of protein tyrosine phosphatase 1B (PTP1B) in macrophages, which accompanied with robust immune activation and marked Janus Kinase 2/Signal Transducer and Activator of Transcription 3 (JAK2/STAT3) signaling pathway inhibition. In tendinopathy mouse models, both pro-inflammatory cytokines and PTP1B were found to be highly expressed in tendon tissues. However, conditional deletion of Ptpn1 (encoding PTP1B, Ptpn1-/-) in macrophages significantly alleviated tendon inflammation and fibrosis, indicating a strong association between PTP1B and tendinopathy. Mechanistically, in vivo experiments demonstrated that macrophage PTP1B suppressed STAT3 activation by inhibiting JAK2 phosphorylation, and inhibited the mitochondrial fusion protein Optic Atrophy1 (OPA1), resulting in mitochondrial fragmentation and mitochondrial DNA (mtDNA) release. This process activated the Cyclic GMP-AMP synthase/Stimulator of interferon genes (cGAS/STING) pathway, elevating the levels of inflammation and exacerbating tendon injury. In summary, macrophage PTP1B was shown to regulate mitochondrial dynamics via the JAK2/STAT3-OPA1 axis and trigger inflammation through activation of the cGAS/STING pathway, representing a key mechanism underlying the progression of tendinopathy. Targeting PTP1B or associated pathways may provide novel therapeutic strategies for tendinopathy.